The Impact of Risk Management on Firm Performance: Corporate Governance as Moderating Variable - Eduard Ary Binsar Naibaho; Ni Made Crivanty Mayayogini (Media Ekonomi dan Manajemen, 2023)
This research aims to examine the impact of risk management, especially operational risk, credit risk, and liquidity risk on firm performance with corporate governance as a moderating variable. The research was conducted using secondary data from 48 companies in the Southeast Asia region which are included in the Consumer Durable and Apparel, Consumer Service, and Consumer Staples industry categories at S&P Capital IQ during the 2017-2021 period. The sample collection technique in this study used a purposive random sampling method. The result of this study finds that operational risk and credit risk do not affect firm performance, while credit risk has a negative effect on firm performance. This study also found that corporate governance can reduce the negative effect of liquidity risk on firm performance but strengthen the relationship between operational risk and credit risk on firm performance. The result found in this study has implications and contribution for the company to develop a good corporate governance in order to maximize the risk management and also for investor to assess the company risks.